Relationships among cultivated peas and their wild relatives: Molecular and morphological characterization - Hanci, Fatih; Cebeci, Esra (Bangladesh Journal of Botany, 2019)
This study was conducted to determine relationship between some wild pea accessions (Pisum fulvum L., P. abyssinicum L., P. sativum var. elatius), local varieties (P. sativum var. sativum L. and P. sativum var. arvense L.) and commercial varieties “Boogie” and “Rondo”. The genetic diversity was evaluated with 14 simple sequence repeat markers and 50 morphological characters. The results of morphology indicated that, genotypes showed a clustering pattern based on the taxonomic groups when considering only flower characters and all morphological characters. During the molecular study, a total of 48 alleles were obtained. Used all primers showed polymorphism in accessions. The number of alleles varied between 2 - 6 among 14 SSR loci revealing the polymorphism level of markers. Similarity coefficient (Dice’s) ranged from 0.100 to 0.800 with an average of 0.378. A dendrogram grouped the 15 genotypes into two main clusters. This information can be utilized for genetic analysis, genotype identification from different sources and development of improved germplasm.